The complete mitochondrial genomes of Macrostylophora euteles and Citellophilus tesquorum sungaris and the phylogenetics of known Siphonaptera mitogenomes - Duan, Mingna; Liu, Yafang; Wu, Jun; Liu, Shuang; Tang, Shaobo; Jiang, Dandan; Zhang, Quanfu; Gu, Wei; Yang, Xing (Frontiers in Veterinary Science, 2025)
Fleas serve as hosts to a diverse array of pathogens, which present significant medical and veterinary concerns for human and livestock health. The mitochondrial genome (mtDNA) has long been regarded as a classical model in biogenetics and species evolution research. However, the availability of mitochondrial genome data for fleas remains scarce. In this study, we sequenced Macrostylophora euteles specimens collected from the Yunnan plague focus and Citellophilus tesquorum sungaris specimens from Jilin plague focus. The obtained sequences were compared to the sequences of 24 flea species retrieved from the NCBI database, focusing on base composition, evolution rates, nucleotide polymorphism and phylogenetic analysis. All fleas analyzed contained a total of 37 genes. Gene sequences exhibited remarkable stability, with no evidence of gene rearrangement. Additionally, the base composition demonstrated a pronounced AT bias. Results from both methodologies and across the two datasets consistently indicated strong monophyly for the superfamilies Ceratophylloidea and Pulicoidea, as well as for the family Pulicidae. In contrast, the superfamily Hystrichopsylloidea, along with the families Ceratophyllidae, Leptopsyllidae and Ctenophthalmidae, were identified as paraphyletic. This research provides valuable molecular data to support taxonomic and phylogenetic studies of fleas.